2011
DOI: 10.1142/s1363919611003350
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Perceived Usefulness of Workplace Social Networks Upon the Innovative Behaviour of Sme Employees: A Social Capital Perspective

Abstract: This research includes an examination about the impact of three organisational factors upon the perceived usefulness of workplace social networks for problem solving in engineering SMEs. As well this research examines the impact of the perceived usefulness of workplace social networks upon the innovative behaviour of engineering SME employees. More specifically, the dimensions of Social Capital Theory are applied as a lens to develop an understanding into the effect of the strength of workplace social network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
1
14
0
1
Order By: Relevance
“…The present results suggest that nurses with higher levels of social capital perceived greater facilitation and support and fewer barriers to EBP adoption, and were more likely to be competent and experienced less difficulty in finding and reviewing evidence, as compared to nurses with lower levels of social capital. Consistent with the results of the current study, Björk and Magnusson () reported a relationship between members’ network connectivity and the quality of innovation ideas, and Xerri and Brunetto () reported a relationship between perceived usefulness of interpersonal networks during work and members’ innovative behavior. In addition, Carmona‐Lavaldo et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present results suggest that nurses with higher levels of social capital perceived greater facilitation and support and fewer barriers to EBP adoption, and were more likely to be competent and experienced less difficulty in finding and reviewing evidence, as compared to nurses with lower levels of social capital. Consistent with the results of the current study, Björk and Magnusson () reported a relationship between members’ network connectivity and the quality of innovation ideas, and Xerri and Brunetto () reported a relationship between perceived usefulness of interpersonal networks during work and members’ innovative behavior. In addition, Carmona‐Lavaldo et al.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, social capital could be facilitated through interactions, such as by engaging in enjoyable activities, sharing affection, or exchanging advice and information. In a study performed in nonhealthcare organizations, social capital was found to have a significant relationship with the presence of an innovative climate (Xerri & Brunetto, ) and with other performance factors such as production innovation, reduced employee turnover, or creation of intellectual capital (Mura et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This initial attempt to understand customer-related outcomes of FLEs' innovative service behavior introduces a neglected phenomenon to innovation research. Most investigations refer to innovative work behavior, in research dedicated to innovation management (Ramamoorthy et al, 2005;Salomo, Talke, and Strecker, 2008;Xerri and Brunetto, 2011), organizational psychology (e.g., Janssen, 2000Janssen, , 2003Michaelis, Stegmaier, and Sontag, 2010;Pieterse et al, 2010;Rank, Nelson, Allen, and Xu, 2009), management, or human resources (Aryee, Walumbwa, Zhou, and Hartnell, 2012;Scott and Bruce, 1994). These studies focus on innovative work behaviors within the firm, as perceived by employees or their supervisors.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…A closely related construct is individual innovative behavior , or “the process of bringing new problem solving ideas into use” (Xerri and Brunetto, , p. 968). It consists of various practices, such as opportunity exploration, idea generation, championing, and application.…”
mentioning
confidence: 99%